(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The current study aimed to assess the cytotoxic potential of doxorubicin (DOX) loaded nanoparticles (NPs) for effective colon cancer targeting. Poly-caprolactone (PCL) was used to make the NPs, and PCL was then conjugated with hyaluronic acid (HA) and polyethylene glycol (PEG) (HA-PEG-PCL NPs). The developed NPs were used to encapsulate the DOX, which was then tested for stability, in-vitro drug release, cell viability, and entrapment effectiveness. The NPs were manufactured with care, and TEM examinations showed that they were spherical. Zeta potential measurements for HA-PEG-PCL and PCL NPs were 16.4±0.84 mV, -4.9±0.3, and PDI 0.648 and 0.553, respectively, for both formulations. HA-PEG-PCL NPs and PCL NPs were found to have particle sizes of 267±0.5 nm and 142±1.5 nm, respectively. The NPs made using HA-PEG-PCL copolymers demonstrated their ability to continue the release of DOX. While DOX-HA-PEG-PCL NPs released 93.1±2.4% of DOX in 96 hrs, DOX-PCL NPs released nearly 100% of the medication in the same time frame. When the stability was assessed in terms of particle size and %EE, it was discovered that the NPs formulations were more stable at 4±2°C and then 28±2°C. Because HA binds to the overexpressed CD44 receptors on HT-29 cells, the DOX-HA-PEG-PCL NPs demonstrated noticeably more cytotoxicity as a result of better formulation internalization. The controlled drug release behaviour of the proposed nanotechnology showed their potential for colon cancer cell lines.